2020
DOI: 10.35799/pha.9.2020.30031
|View full text |Cite
|
Sign up to set email alerts
|

UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL BULBUS BAWANG DAYAK (Eleutherine americana Merr) DENGAN METODE DPPH (1,1-Diphenyl-2-Picrylhydrazyl)

Abstract: Dayak onion plant (Eleutherine americana Merr.) or commonly called forest onion is a typical plant of Central Kalimantan that has been used by local peoples for cure a various types of diseases. This study aims to determine the activity of antioxidant compounds from Dayak bulb ethanol extracts from Kotamobagu City. This research method is an experimental laboratory. Initially the Dayak bulb sample was extracted maceration with 96% ethanol solvent then evaporated until a thick extract was obtained. As a paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…to 2 ml and homogenized. 15 Preparation of test solutions for nanoemulsion preparations of grape seed oil and clove ethanol extract was done as follows: a nanoemulsion stock solution was made by weighing 500 mg of the nanoemulsion sample and then dissolving it in 50 ml of ethanol p.a. (10,000 ppm), a concentration of 400 was made; 600; 800; 1,000; and 1,200 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…to 2 ml and homogenized. 15 Preparation of test solutions for nanoemulsion preparations of grape seed oil and clove ethanol extract was done as follows: a nanoemulsion stock solution was made by weighing 500 mg of the nanoemulsion sample and then dissolving it in 50 ml of ethanol p.a. (10,000 ppm), a concentration of 400 was made; 600; 800; 1,000; and 1,200 ppm.…”
Section: Methodsmentioning
confidence: 99%
“…Three ml of extract or BHT was put into a test tube, and 1 ml of DPPH solution was added. The solution was incubated (30 minutes) and the absorbance at the maximum DPPH wavelength obtained was measured [12]. The percent inhibition at various concentration was regressed to obtain linear regression values and IC50 values.…”
Section: Antioxidant Activity Testmentioning
confidence: 99%
“…Chemical compounds found in dayak onion include 15 compounds, including flavonoid derivatives and naphthoquinones [13]. High antioxidant activity is attributed to flavonoid compounds [14], indicating that dayak onion has a high antioxidant activity against free radicals. Another study by Gayatri et al found that administering ethanol extract of dayak onion at doses of 30, 60, and 120 mg/kg BW to male mice induced with lead acetate for 35 days increased the diameter of seminiferous tubules in mice [15].…”
Section: Introductionmentioning
confidence: 99%